Understanding Volatility dependence between MENA Sukuk, GCC Sukuk and Nifty Shariah Index during Covid-19: A C-vine Copula Approach - Siddiqui, Saif; Rizvi, Ziya Batool (European Journal of Islamic Finance, 2022)
The study aims to find out the volatility dependence between MENA Sukuk , GCC Sukuk ,and Nifty 50 Shariah indices. Further, it finds out volatility pattern among the same indices before and during COVID-19 pandemic. Daily data (April 2017 to November 2020) of the indices are analyzed using the GARCH model and C-Vine Copula approach. It is done by modeling the returns of the indices. In pre Covid period- C Vine copula shows that the Sukuk have strong dependence while Shariah index has rather weak dependence, for MENA Sukuk and Nifty Shariah 50 it increased by a great margin in during-COVID 19 periods. GCC Sukuk and Nifty Shariah indices are positively correlated to each other in comparing to returns of Mena Sukuk. The results of the GARCH model show asymmetrical co movements for losses and gains. Moreover, conditioned on MENA Sukuk, the GCC Sukuk and Nifty Shariah 50 had a higher negative degree of dependence within and throughout COVID-19 period. There is ample work available on various Islamic indices but there is dearth study found on the S&P Middle East and North Africa (MENA) Sukuk, GCC Sukuk and Nifty Shariah 50 indices, together. It fills the gap in the literature. Keywords: Covid-19, Dependency, Volatility, Sukuk, Index, Copula, GARCH. Paper type: Empirical paper Funding: This research did not receive any grant from funding agencies in the public, commercial, or not-for-profit sectors.